Wielość światów. Kilka refleksji o twórczości lirycznej Pavla Straussa - Dambek, Małgorzata (Slavia Occidentalis, 2016)
Writer Pavol Strauss is little known in Slovakia and Poland because there were several decades between his first collections of poetry written in the German language in the period between the two World Wars and his Slovak post-war essays, and then his other works (essays, diaries and aphorisms) published sporadically or after 1989 on the other. He published four collections of poetry in German: Die Kanone auf dem Ei (1936), Schwarze Verse (1937), Worte aus der Nacht (published bilingually in 2001) and Bruder Abel lebt ja noch (manuscript). After 1946 Pavol Strauss stopped writing poetry and stopped writing in German.